1999
DOI: 10.2307/2657235
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Processes in Structured Fish Populations: Interaction Strengths in Whole-Lake Experiments

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Sun, Abstract. The goal of this study is to identify the mechanisms and measure the strengths of interactions within and among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
249
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(268 citation statements)
references
References 70 publications
13
249
6
Order By: Relevance
“…We conducted only a single netting trial for habitat use to minimize killing fishes that had survived, because vulnerability to gillnets (and therefore mortality) increases with body size (Biro et al 2003a). Rainbow trout of the size used in this experiment primarily eat zooplankton, which is most abundant in the open-water, or pelagic, habitat (Post et al 1999). We assumed that the pelagic habitat was the most risky based on previous work showing avoidance of this habitat by trout (Post et al 1999), the absence of any physical structure into which they could escape, and focal animal observations of loons which indicated that loons initiate their foraging dives in the pelagic habitat (C. Beckmann, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted only a single netting trial for habitat use to minimize killing fishes that had survived, because vulnerability to gillnets (and therefore mortality) increases with body size (Biro et al 2003a). Rainbow trout of the size used in this experiment primarily eat zooplankton, which is most abundant in the open-water, or pelagic, habitat (Post et al 1999). We assumed that the pelagic habitat was the most risky based on previous work showing avoidance of this habitat by trout (Post et al 1999), the absence of any physical structure into which they could escape, and focal animal observations of loons which indicated that loons initiate their foraging dives in the pelagic habitat (C. Beckmann, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Rainbow trout of the size used in this experiment primarily eat zooplankton, which is most abundant in the open-water, or pelagic, habitat (Post et al 1999). We assumed that the pelagic habitat was the most risky based on previous work showing avoidance of this habitat by trout (Post et al 1999), the absence of any physical structure into which they could escape, and focal animal observations of loons which indicated that loons initiate their foraging dives in the pelagic habitat (C. Beckmann, unpublished data). We surveyed the loon lakes over 6 days immediately after stocking, 5 days during the netting trial in the latter half of June, and 4 days in mid-July.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Progeny from both pure hatchery and hatchery-wild crosses were assigned to the hatchery subpopulation to account for the often-reported reduced fitness in hatchery fish or hybrids relative to wild fish (30,31). Prestocking early YOY numbers of each subpopulation were determined by a Ricker stock-recruitment function (22), resulting in densitydependent survival regulated by ecological competition, as is typical in nature (7,32). A recruitment deviate added stochasticity that propagated through later life stages, resulting in natural population fluctuation (26).…”
Section: Model Overviewmentioning
confidence: 99%